Pembaharuan Kurikulum di Pondok Pesantren Al-Irsyad Islamic Boarding School Bulaan Kamba - Rahimmatul Hayati; Rengga Satria (Program studi Keagamaan Islam, 2022)
This research aim to find out, explain, and to describe how the renewal of Islamic education in the field of curriculum at al-Isyad Islamic Boarding School Bulaan Kamba, Kubang Putiah (years 2011 until 2021). Including the renewal of the study of yellow book. The location of this research is the Islamic Boarding School al-Irsyad Islamic Boarding School Bulaan Kamba, Kubang Putiah Village, Banuhampu District, Agam Regency. This type of research is a qualitative research with historical research methods. This research was conducted at the Islamic Boarding School al-Irsyad Islamic Boarding School Bulaan Kamba, Kubang Putiah, Banuhampu District, Agam Regency. Data collection techniques were carried out by observation, interviews, and documentation. Data analysis techniques using data reduction, data presentation and data verification. Technique of validating data with triangulation technique. The results of the research conducted by the researchers can be concluded that there is indeed a renewal of Islamic education in the al-Irsyad Islamic Boarding School Bulaan Kamba Islamic Boarding School, Kubang Putiah, especially in the field of curriculum. Renewal is also seen in the study of the yellow book as a source of learning in the daily cottage. The difference between the research that the researcher did and the previous research lies in the object under study